2015
DOI: 10.1177/2042018815600640
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D as a risk factor for premature atherosclerosis in patients with type 2 diabetes

Abstract: Background: Several cardiovascular risk factors have been recognized in patients with diabetes and vitamin D deficiency is emerging as a new risk. The aim of this study was to determine the effect of vitamin D deficiency on the incidence of premature atherosclerosis in patients with type 2 diabetes. Methods: A total of 78 patients with type 2 diabetes were subjected to history taking, physical examination, fasting glucose level, homeostasis model assessment of insulin resistance, lipid profile, 25(OH) vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Main summary of the characteristics of the included studies are described in ▶ Tables 1-3. A total of 22 studies published from 2006 to 2017 covering a total of 7332 human participants, from studies in different countries (Korea [15], Italy [16][17][18][19][20], Sweden [21], China [22][23][24][25][26][27], USA [28,29], Egypt [30], Scandinavian [31], Turkey [1], Iran [7,32], Bulgaria [33], and UK [34]) with age ranging from 18 to 75 years, were identified in this meta-analysis. Most of the participants were women.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Main summary of the characteristics of the included studies are described in ▶ Tables 1-3. A total of 22 studies published from 2006 to 2017 covering a total of 7332 human participants, from studies in different countries (Korea [15], Italy [16][17][18][19][20], Sweden [21], China [22][23][24][25][26][27], USA [28,29], Egypt [30], Scandinavian [31], Turkey [1], Iran [7,32], Bulgaria [33], and UK [34]) with age ranging from 18 to 75 years, were identified in this meta-analysis. Most of the participants were women.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…There were 17 studies reported the mean serum level of vitamin D and correlation coefficients between association serum vitamin D level and CIMT. Participants were outpatients who underwent eco-Doppler examination of the extra cranial carotid tract [17], pa-tients with mild primary hyperparathyroidism (PHPT) without any known cardiovascular risk factors [21], patients with type 2 diabetes [16,23,27,30], adults with hypertension [29], high-risk cardiac patients [25], patients with obstructive sleep apnea syndrome (OSA) [31], subjects with high cardiovascular risk [34], middle-aged and elderly men [24], postmenopausal women [22,26], post-menopausal women with Sjogren's syndrome [20], adults with growth hormone deficiency [33], subjects with pre-diabetes [19], patients with Behcet's disease [18] and patients with subclinical carotid atherosclerosis [34]. Forest plot displaying the effect of vitamin D supplementation on CIMT is shown in ▶ Fig.…”
Section: Correlation Between Serum Vitamin D Levels With Cimtmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased vitamin D levels were associated with increased CIMT ( 6 ) , insulin resistance and inflammation ( 7 ) . Furthermore, Braam et al ( 8 ) found that long-term supplementation with vitamins K 1 (1 mg) and D (8 µg) had beneficial effects on elastic properties of the carotid artery in postmenopausal women, but it did not influence CIMT.…”
mentioning
confidence: 99%
“… 40 Hamdy Al-Said et al also found that hypovitaminosis in diabetic patients may be a risk factor for premature atherosclerosis assessed from the increase in intima-media thickness of the carotid artery in patients with T2DM. 41 An Italian study showed that hypovitaminosis D was independently associated with an increased prevalence and severity of coronary artery disease. 42 The roles of hypovitaminosis D in increasing the risk of cardiovascular diseases could be direct or indirect.…”
Section: Discussionmentioning
confidence: 99%